PENGARUH KUALITAS TEKNIS DAN KUALITAS FUNGSIONAL TERHADAP KEPERCAYAAN NASABAH (STUDI KASUS NASABAH BANK BUKOPIN CABANG BEKASI) - Mulyanti, Kurniawati (Fakultas Ekonomi Universitas Islam 45, 2011)
Before buying or consuming good and services, The Consumers will consider evaluation result of services quality that it?s perceived when they consume good and services. If they feel good and satisfied with the services so the consumer will belief to buy and consume and they belief with the services that it?s enjoyed. The bank, as financial institusion is greatly influenced trust of customer. Therefore, the factors affecting of the trust very important to paid attention and improved. The technical quality and functional quality that it?s do by the bank will influence trust of the customers for the institution. The research discuss influence of technical quality and functional quality on customers confidence in Bank Bukopin especially Bekasi branch. The technical quality refer to skill or expertise of customer services and supporting factors requite saving results. Whereas, the functional quality refer to interaction process of customer services with customers when they transaction. The result of the study explain there is a positive influence and significant of technical quality variable and functional quality on customers confidence. The research use respondent data as many as 81 people. The result of the study recommends for bank Bukopin management to attention on aspects related with technical quality and functional quality in order to achieve customer confidence,paper investigates the implemented a new Rpl,00 tick size on December 16, 2006 in the Indonesia Stock Exchange.